Variasi Biokimia Genetik Populasi Ikan Betutu (Oxyeleotris marmorata, BLKr.) di Waduk Penjalin Brebes - Agus Hery Susanto; Suhestri Suryaningsih (Universitas Atma Jaya Yogyakarta, 2006)
Penjalin water reservoir in Brebes Regency, Central Java, is one of the habitats of the sand goby. A study on its genetic diversity using approaches of isozyme analysis was needed to support domestication of the fish in this area. This study was aimed at the biochemical-genetic variation of sand goby population in Penjalin water reservoir based on esterase (EST), peroxidase (PER), malate dehydrogenase (MDH), aspartate amino-transferase (AAT), and acid phosphatase (ACP) polymorphisms. Visualization of the isozymes was carried out employing horizontal electrophoretic technique with potato starch gel and buffer system of L-histidin monohydrate. Of the five isozymes, ACP was not well-visualized in all samples tested while the remaining four showed no polymorphisms. It could be concluded that there is no biochemical-genetic variation of sand goby population in Penjalin water reservoir based on isozymes of EST, PER, MDH, and AAT.